The Impact of Management Accounting Information Systems and Accounting Information Quality on Managerial Performance: Internal Control as a Moderating Factor - Ammy, Baihaqi; Nadia, Sindi (Jurnal EMT KITA, 2026)
This study analyzes the influence of Management Accounting Information Systems (MAIS) and Accounting Information Quality (AIQ) on Managerial Performance, with Internal Control (IC) as a moderating variable at PT. Metinca Prima Industrial Works. Issues regarding the effectiveness of MAIS and AIQ in improving performance, as well as the crucial role of IC, still require empirical exploration, particularly within the Indonesian manufacturing industry context. This quantitative study utilized primary data collected through a survey of 85 relevant managers and accounting/finance staff (from a total population of 405). Data were analyzed using Partial Least Squares – Structural Equation Modeling (PLS-SEM) with SmartPLS. The results indicate that MAIS significantly and positively impacts Managerial Performance (β = 0.241, p = 0.031). Similarly, AIQ also significantly and positively impacts Managerial Performance (β = 0.426, p = 0.001). Furthermore, IC was found to significantly moderate the relationship between MAIS and Managerial Performance, and to significantly moderate the relationship between AIQ and Managerial Performance. The research model explains 61.1% of the variance in Managerial Performance (R2 = 0.611), demonstrating good predictive power. These findings underscore the importance of effective MAIS and AIQ in enhancing managerial performance, and highlight the role of IC in shaping these relationships. This study offers theoretical contributions and practical implications for the management of PT. Metinca Prima Industrial Works to optimize information systems and controls for improved performance.